2006
DOI: 10.1159/000093949
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Controlled Trial of a Collaborative Care Model with Psychiatric Consultation for Persistent Medically Unexplained Symptoms in General Practice

Abstract: Background: Patients with persistent medically unexplained symptoms often exhibit general dysfunction and psychiatric comorbidity and frequently resist psychiatric referral. The aim of this study was to evaluate the efficacy of a collaborative care model including training for general practitioners (GPs) and a psychiatric consultation model for patients with persistent medically unexplained symptoms in general practice. Method: Randomised controlled trial. Cluster randomisation at GP practices and multilevel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 72 publications
3
93
0
6
Order By: Relevance
“…The high prevalence of this syndrome indirectly confirms the widespread somatic presentation of psychiatric distress in non-specialist medical settings reported by other authors [19,56,57,58,59]. This finding is also consistent with the excess utilization of PC services by patients with subsyndromal somatization symptoms [60].…”
Section: Discussionsupporting
confidence: 88%
“…The high prevalence of this syndrome indirectly confirms the widespread somatic presentation of psychiatric distress in non-specialist medical settings reported by other authors [19,56,57,58,59]. This finding is also consistent with the excess utilization of PC services by patients with subsyndromal somatization symptoms [60].…”
Section: Discussionsupporting
confidence: 88%
“…Patients with FSS may be treated effectively with psychotherapy provided by specialists [13,14,15,16]. However, for capacity reasons and because early intervention could be more cost-effective and prevent chronification of the condition, pragmatic primary care trials with GPs as therapists are needed [17].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, psychiatric intervention studies have been conducted with the aim to improve health outcome in patients with somatic and psychiatric comorbidities [8, 10, 11]. While some of these studies demonstrated a beneficial effect on psychosocial and medical outcomes [12,13,14] and health care utilization [15, 16], others showed only minor or no effects [17].…”
Section: Introductionmentioning
confidence: 99%